2015
DOI: 10.1108/ijlm-01-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shipping knowledge and absorptive capacity on organizational innovation and logistics value

Abstract: Purpose – The purpose of this paper is to examine what types of shipping knowledge are crucial in order for shipping companies to survive in dynamic business environment, and to investigate how the shipping knowledge affects the company’s performance (i.e. organizational innovation and logistics value). This paper also diagnoses the moderating effect of absorptive capacity on the relationship between the shipping knowledge and its effectiveness. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…In the selected six quantitative studies [35][36][37][38][39][40] and five qualitative studies [41][42][43][44][45] as shown in Figure 8, different analysis techniques were used to investigate the effects on performance as dependent variables: structural equation modelling (SEM) in the half of the studies, linear modelling (e.g., regression analysis) and an analytical network process with a quality deployment function.…”
Section: Evidence-based Actions On How To Enhance Performancementioning
confidence: 99%
“…In the selected six quantitative studies [35][36][37][38][39][40] and five qualitative studies [41][42][43][44][45] as shown in Figure 8, different analysis techniques were used to investigate the effects on performance as dependent variables: structural equation modelling (SEM) in the half of the studies, linear modelling (e.g., regression analysis) and an analytical network process with a quality deployment function.…”
Section: Evidence-based Actions On How To Enhance Performancementioning
confidence: 99%
“…In addition, high product variety often implies that online sellers offer many different product categories. Since each product category may have different logistics requirements, a seller's lack of specialization, knowledge and expertise may decrease LSQ (Fernhaber and Patel 2012;Lee and Song 2015). Therefore, the second hypothesis is developed as follows:…”
Section: Research Hypothesesmentioning
confidence: 99%
“…According to this purpose, the desired goal is to explore ways to develop cost-efficient, agile transport networks, to improve sea and inland communication nodes, to facilitate maritime stakeholders' interactions and upgrade the quality of port SCSs by managing risks (Panayides & Song, 2013). Maritime logistics value and innovativeness are important assets for long-term organisational performance in the maritime shipping industry (Lee & Song, 2015). Adopting KM strategies in maritime logistics can leverage these assets.…”
Section: Knowledge Management In Maritime Logisticsmentioning
confidence: 99%
“…Knowledge management (KM) has attracted great attention from maritime logistics specialists as a means to facilitate organisational learning (Lee & Song, 2015) to discover new practices and implementations in their supply chain operations and thus to improve their business know-how. The management of knowledge is considered a "strategic asset" (Durst & Evangelista, 2016), which has the potential to advance the MLoSC performance.…”
Section: Introductionmentioning
confidence: 99%